PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP INTENSITAS NYERI PADA IBU BERSALIN KALA I DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM TAHUN 2023 - Putri Oktadini; Siti Husaidah, Ns. Resi Novia (Jurnal Kesehatan, 2024)
Labor pain is a feeling of discomfort associated with uterine contractions, cervical dilatation and effacement, decreased presentation, stretching of the vagina and perineum which ends in the fourth stage of labor. Murottal Al-Qur'an can increase the release of endorphins so that the pain threshold decreases. The aim of this research was to determine the effect of Al-Qur'an murottal therapy on the intensity of pain in the first stage.This type of research is pre-experimental design using one group pretest-post test design. The sample in this study was 15 mothers in the first stage of labor who experienced labor pain in the working area of the Sei Langkai health center, Batam City, taken using a purposive sampling technique. The data analysis technique uses the T-test.The results of the study showed that the mean value of the pain level of mothers in the first stage of labor before being given the Al-Qur'an murottal was (2.87), then there was a decrease in the mean after being given the Al-Qur'an murottal to (2.00). The statistical test results have a p-value = 0.00 (<0.05), meaning that there is a significant influence between the level of dysmenorrhea before and after being given the Al-Qur'an murottal intervention to mothers in the first stage of labor who experienced labor pain in the working area of the Sei Langkai health center. Batam city.The conclusion of this study is that there is a significant influence between the level of labor pain before and after being given Al-Qur'an murottal intervention to women in the first stage of labor who experience labor pain in the working area of the Sei Langkai health center, Batam City. It is hoped that BPM can carry out Al-Qur'an murottal 'an as a non-pharmacological therapy reduces pain in the first stage of labor.